Bunocephalus hertzi, a new banjo catfish from the upper Rio Paraná basin, Brazil (Siluriformes: Aspredinidae), with the redescription of Bunocephalus larai Ihering, 1930 - Esguícero, André L. H.; Castro, Ricardo M. C.; Pereira, Thiago N. A. (Zootaxa, 2020)
Bunocephalus hertzi, new species, is described from two tributaries of the upper Rio Paraná basin. Because the type series of B. larai (the only other species of Bunocephalus in the basin) is lost, a redescription of B. larai is also provided herein. Bunocephalus larai and B. hertzi can be distinguished from all its congeners, except B. minerim, by the absence of an epiphyseal bar (vs. present). From B. minerim, both species can be distinguished by the presence of 10 principal caudal-fin rays (vs. 9). Bunocephalus hertzi can be differentiated from B. larai by the longer coracoid process size (11.9–16.2% vs. 6.7–9.8% SL), shorter maxillary barbel (just reaching the pectoral fin origin; 54.6–67.4% vs. 73.7–84.6% HL) and skull ornamentation represented by five bony protuberances between the posterior end of the occipital and the origin of the dorsal fin (vs. four bony protuberances).